2015
DOI: 10.1021/acs.jpcc.5b01527
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Ordering of Conjugated Polymers at Metallic Interfaces Probed by SFG Vibrational Spectroscopy

Abstract: Organic−metal interfaces play a fundamental role in charge injection to organic electronic devices, and their performance significantly affects the device efficiency. Therefore, these interfaces have been studied by numerous experimental techniques, but most of them are either not strictly interface-specific or require special samples, with ultrathin metal or molecular coatings, which may not be representative of real devices. Here we use sum-frequency generation vibrational spectroscopy (SFG-VS), a surface-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 66 publications
2
24
0
Order By: Relevance
“…This approach is similar to recent SFG studies of the C C stretching mode of polythiophene films for determining interfacial ring orientation. 50 52 The molecular frame used for the pyrylium core follows standard convention with the molecular c -axis lying along the direction of the net transition dipole (which falls in the average plane of the core), the a -axis also is in the plane of the pyrylium backbone and is oriented along the two aromatic units, and the b -axis is orthogonal to a and c . It is not expected that the selenophene substituents will induce a meaningful distortion to this symmetry and are left out of the SFG orientation calculation for the 1600 cm –1 mode for simplicity.…”
Section: Resultsmentioning
confidence: 99%
“…This approach is similar to recent SFG studies of the C C stretching mode of polythiophene films for determining interfacial ring orientation. 50 52 The molecular frame used for the pyrylium core follows standard convention with the molecular c -axis lying along the direction of the net transition dipole (which falls in the average plane of the core), the a -axis also is in the plane of the pyrylium backbone and is oriented along the two aromatic units, and the b -axis is orthogonal to a and c . It is not expected that the selenophene substituents will induce a meaningful distortion to this symmetry and are left out of the SFG orientation calculation for the 1600 cm –1 mode for simplicity.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, non-linear optical spectroscopic techniques such as second-harmonic generation (SHG) and sum-frequency generation vibrational spectroscopy (SFG) have a good potential to investigate interfaces in organic electronics (Motti et al, 2014; Maia and Miranda, 2015), but have not been extensively used so far. Since they rely on broken inversion symmetry, they could, in principle, probe the vertical phase segregation in a photovoltaic blend, since in a homogeneous blend there is inversion symmetry (on the scale of optical wavelengths), while at an interface this symmetry is broken.…”
Section: Interfacial Morphologymentioning
confidence: 99%
“…The results also showed that spontaneous charge transfer between metal and CP was affected by the polymer molecular arrangements (Figure 10c). 100 A study of the epoxy/copper interface correlated the interfacial molecular structures of the epoxy and the adhesion promoters with the mechanical adhesion strength of such interfaces. 101…”
Section: The Study Of Polymer/metal Interfacesmentioning
confidence: 99%
“…99 In another study, a similar sandwiched geometry was used to investigate the molecular ordering of conjugated polymers (CPs) at metal interfaces. 100 It was found that polymer orientations were different at two types of CP/metal interfaces: metal evaporated on the CP, and CP spin coated on the metal. The results also showed that spontaneous charge transfer between metal and CP was affected by the polymer molecular arrangements (Figure 10c).…”
Section: The Study Of Polymer/metal Interfacesmentioning
confidence: 99%
See 1 more Smart Citation